Nano-electro-mechanical pump: Giant pumping of water in carbon nanotubes - Farimani, Amir Barati (Sci Rep, 2016)
A fully controllable nano-electro-mechanical device that can pump fluids at nanoscale is proposed. Using molecular dynamics simulations, we show that an applied electric field to an ion@C60 inside a water-filled carbon nanotube can pump water with excellent efficiency. The key physical mechanism governing the fluid pumping is the conversion of electrical energy into hydrodynamic flow with efficiencies as high as 64%. Our results show that water can be compressed up to 7% higher than its bulk value by applying electric fields. High flux of water (up to 13,000 molecules/ns) is obtained by the electro-mechanical, piston-cylinder-like moving mechanism of the ion@C60 in the CNT. This large flux results from the piston-like mechanism, compressibility of water (increase in density of water due to molecular ordering), orienting dipole along the electric field and efficient electrical to mechanical energy conversion. Our findings can pave the way towards efficient energy conversion, pumping of fluids at nanoscale, and drug delivery.